Prevalence of Mineral Bone Disorders in Chronic Kidney Disease Patients (Academia Journal of Medicine, 2019)
Background: Chronic kidney disease (CKD) is a progressive loss in renal function which involves in deterioration in mineral homeostasis  with disruption of normal serum and tissue concentration of phosphorus and calcium. Also changes in circulating levels of hormones parathyroid hormone (PTH), calcitriol (1,25(OH)2 D), and fibroblast growth factor-23 (FGF-23). Here our aim is to study the prevalence of  markers associated with MBD in CKD stage 3-5 patients. Patients with CKD stage 3-5 were included in this observational study with all  necessary parameter. X-RAY abdomen and echocardiography was done to look for evidence of vascular and valvular calcification  respectively. Statistical analysis was done using SPSS software. A total of 170 patients (128 males, 42 females) (M:F = 3:1) were included in  this study with a mean age of 50.54 years. Among CKD stages 3 to 5, the prevalence of hypocalcemia was 22.2%, 33.3% & 48.9%,  hyperphosphatemia was 11.1%, 25.5% & 63%, hyperparathyroidism was 48.1%, 67.3% & 89.1%, high total alkaline phosphatase was 0%,  5.9% & 45.7% , low 25-OH-vit D was 59.2%, 70.6% & 79.4% respectively. Low 25 (OH) D levels, hyperparathyroidism, and  hyperphosphatemia were the noticeable markers of CKD-MBD in our patients. Mineral bone disorder are common in CKD patients which start  in early CKD stages & worsen with disease progression that causes morbidity and decreased quality of life.
Keywords: CKD; MBD; Hyperparathyroidism; Hyperphosphatemia; Hypocalcemia